2019
DOI: 10.1186/s12889-019-7331-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a breastfeeding support programme on breastfeeding duration and exclusivity: a quasi-experiment

Abstract: Background Breastfeeding has important positive long-term health consequences for infants and mothers. The World Health Organization recommends that all infants should be exclusively breastfed for six months or longer, and advises continuation of breastfeeding for two years or beyond. However, these recommendations are not met in many countries. This study examined whether a comprehensive, evidence-based breastfeeding intervention, the Breastfeeding Support Programme (BSP), promotes prolonged dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 38 publications
2
49
0
4
Order By: Relevance
“…It can be inferred from this that, although the subjects studied present some previous difficulty related to BF, the support offered by breastfeeding consultancy acted in solving this demand, increasing the proportion of mothers and children in EBF. A quasi-experiment conducted in the Netherlands corroborates the assertion that the intervention by individuals trained by the IBCLC is effective in increasing the duration and exclusivity of breastfeeding, as well as in delaying weaning (5) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It can be inferred from this that, although the subjects studied present some previous difficulty related to BF, the support offered by breastfeeding consultancy acted in solving this demand, increasing the proportion of mothers and children in EBF. A quasi-experiment conducted in the Netherlands corroborates the assertion that the intervention by individuals trained by the IBCLC is effective in increasing the duration and exclusivity of breastfeeding, as well as in delaying weaning (5) .…”
Section: Discussionsupporting
confidence: 55%
“…Studies in Italy and the Netherlands, as well as a systematic review and meta-analysis, have already shown the superiority of a consultant's role in improving breastfeeding outcomes (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In their systematic review of professional support interventions for breastfeeding, Hannula et al reinforced the importance of providing obstetric professionals with educational tools to support breastfeeding which would in turn improve the women's self-efficacy and power to ensure better breastfeeding behavior [30]. In their recently published study, Van Dellen et al examined the association between breastfeeding practice and a comprehensive evidence based intervention named "Breastfeeding Support Program (BSP)" that combines antenatal and postpartum support and education, and concluded that BSP promotes longer duration and higher exclusivity of breastfeeding among their participants [31]. Besides obstetric care providers, neonatal care providers including neonatologists and nurse practitioners should frequently receive enough education and reminders to support breastfeeding to ensure compliance with Step 2 of the BFHI [8].…”
Section: Discussionmentioning
confidence: 99%
“…examined the association between BF practice and a comprehensive evidence based intervention named "Breastfeeding Support Program, BSP" that combines antenatal and postpartum support and education, and concluded that BSP promotes longer duration and higher exclusivity of BF among their participants [29]. Additionally, the strong association between husband's support and intention to breastfeed among the women in our culture makes us believe that husbands should attend the antenatal and postnatal educational sessions about BF as their influences might have a great impact on their wives' intentions.…”
Section: Discussionmentioning
confidence: 99%